Label-free multimodal nonlinear optical microscopy reveals features of bone composition in pathophysiological conditions - Benedetta Talone; Arianna Bresci; Francesco Manetti; Federico Vernuccio; Alejandro De la Cadena; Chiara Ceconello; Maria Lucia Schiavone; Stefano Mantero; Stefano Mantero; Ciro Menale; Renzo Vanna; Giulio Cerullo; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Bone tissue features a complex microarchitecture and biomolecular composition, which determine biomechanical properties. In addition to state-of-the-art technologies, innovative optical approaches allowing the characterization of the bone in native, label-free conditions can provide new, multi-level insight into this inherently challenging tissue. Here, we exploited multimodal nonlinear optical (NLO) microscopy, including co-registered stimulated Raman scattering, two-photon excited fluorescence, and second-harmonic generation, to image entire vertebrae of murine spine sections. The quantitative nature of these nonlinear interactions allowed us to extract accurate biochemical, morphological, and topological information on the bone tissue and to highlight differences between normal and pathologic samples. Indeed, in a murine model showing bone loss, we observed increased collagen and lipid content as compared to the wild type, along with a decreased craniocaudal alignment of bone collagen fibres. We propose that NLO microscopy can be implemented in standard histopathological analysis of bone in preclinical studies, with the ambitious future perspective to introduce this technique in the clinical practice for the analysis of larger tissue sections.